Monitoring of the electrochemical oxidation of venlafaxine and its metabolite o-desmethylvenlafaxine using a flow cell and high-resolution mass spectrometry - Melanie Voigt; Jean-Michel Dluziak; Nils Wellen; Victoria Langerbein; Martin Jaeger (Environmental Sciences Europe)
Abstract Background The antidepressant venlafaxine and its metabolite o-desmethylvenlafaxine are frequently found in water bodies around the world reaching several micrograms per liter. As a remedy, electrochemical advanced oxidation processes (EAOPs) such as anodic oxidation with a boron-doped diamond (BDD) electrode have proven to be a suitable means to prevent entrance in the aquatic environment. For potential application, optimization of the EAOPs can be readily achieved by variation of the conditions using a flow cell as compared to a batch-mode cell. Monitoring and characterization of the reactants provide inside into the oxidation mechanism. Results High-performance liquid chromatography and high-resolution mass spectrometry led to the observation of five transformation products of venlafaxine and to four of o-desmethylvenlafaxine. Mass voltammograms were recorded from which the impact of the oxidation conditions on the degradation and the quantity and nature of transformation products were derived. The transformation pathways were identified as well. Detailed analysis revealed that hydroxyl radicals played the major role in the electrochemical oxidation of venlafaxine and o-desmethylvenlafaxine. The prevalence of the hydroxyl radical induced degradation was further corroborated by the radical scavenger tert-butanol, causing a decrease in elimination efficiency. Both drugs were best eliminated at pH 3 and a voltage of 1.5 V, with the least ecotoxicological concern as indicated by QSAR analysis. Conclusion The study shall contribute to the advancement of EAOPs for advanced stages in wastewater purification treatment. An in silico ecotoxicity assessment using QSAR analysis showed that electrochemical oxidation is beneficial from an ecotoxicological point of view. Especially products formed via the indirect hydroxyl radical-induced mechanism showed a lower ecotoxicity than the initial compound. Graphical Abstract